2009
DOI: 10.1017/s0033291709991541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomical heterogeneity in autistic spectrum disorder: a structural MRI study

Abstract: Adults with ASD have significant differences from controls in the anatomy of brain regions implicated in behaviours characterizing the disorder, and this differs according to clinical subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 62 publications
6
106
4
1
Order By: Relevance
“…This is in accord with many previous VBM studies (Abell et al 1999;Boddaert et al 2004;Brieber et al 2007;Salmond et al 2007;Ke et al 2009;Dziobek et al 2010;Kosaka et al 2010;Toal et al 2010;Riva et al 2011;Via et al 2011;Yu et al 2011). However, other studies have found gray matter increases in some of these and other regions in ASD, making the current picture on structural brain differences in ASD somewhat inconsistent (Amaral et al 2008).…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in accord with many previous VBM studies (Abell et al 1999;Boddaert et al 2004;Brieber et al 2007;Salmond et al 2007;Ke et al 2009;Dziobek et al 2010;Kosaka et al 2010;Toal et al 2010;Riva et al 2011;Via et al 2011;Yu et al 2011). However, other studies have found gray matter increases in some of these and other regions in ASD, making the current picture on structural brain differences in ASD somewhat inconsistent (Amaral et al 2008).…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witsupporting
confidence: 87%
“…Interestingly, morphological changes such as reduced gray matter volume have been reported in ASD in both these regions (Boddaert et al 2004;Brieber et al 2007;Salmond et al 2007;Ke et al 2009;Toal et al 2010;Via et al 2011;Yu et al 2011). The question arises whether the variation of social behavior deficits and of other behavioral aspects of ASD can be related to the morphology of brain regions associated with the disorder.…”
mentioning
confidence: 99%
“…On the other hand, the sparse literature on CC volume in low-functioning ASD (Riva et al 2011) prevents us from drawing inferences about the influence of IQ on CC volume and calls for further investigation. Only a relatively few studies did not reveal significant CC volume differences between ASD patients and typically developing controls; in particular, this finding has been reported more often in voxel-based morphometry (Waiter et al 2004;Bonilha et al 2008;Ke et al 2008;Ecker et al 2010;Toal et al 2010;Cheng et al 2011;Mengotti et al 2011;Calderoni et al 2012) than in region of interest-based (Hong et al 2011) analyses. Notably, to our knowledge, there have been no published studies reporting volumetric increase of CC (Table 1).…”
mentioning
confidence: 92%
“…Investigaciones posteriores señalaron resultados similares en adolescentes y adultos con este síndrome (O'Brien et al, 2010;Murphy et al, 2012). Sin embargo, Toal et al (2010) y Yu et al observaron reducción de la sustancia gris en hipocampos de individuos adultos con SA en comparación con los controles.…”
Section: Características Neuroanatómicasunclassified